The genus Nemoura (Plecoptera: Nemouridae) from Shennongjia National Park of Hubei, China - Li, Mengyu; Bakumenko, Oiha; Yang, Ding; Li, Weihai (Zootaxa, 2024)
Two new species of nemourid stonefly genus Nemoura, N. liuqifeii sp. nov. and N. shennongjia sp. nov., are described from Shennongjia National Park, Hubei Province of south-central China. The relationships between the new species and similar species in the genus are discussed. Three females of an undetermined Nemoura are also described from the park, however, they were not successfully associated with the new species or previously barcoded species.